Role of Trachemys scripta elegans in polystome (Platyhelminthes, Monogenea, Polystomatidae) spillover and spillback following the trade of freshwater turtles in southern Europe and North America - Verneau Olivier; Quinn Dennis; Smith Kevin G.; Malone John H.; du Preez Louis (Parasite)
The red-eared slider, Trachemys scripta elegans (Wied, 1938), has been introduced worldwide, partly because of the exotic pet trade in the 1980s and 1990s. When T. s. elegans is released or escapes into natural environments, it often establishes new feral populations due to its tolerance for a variety of aquatic ecosystems. Therefore, it is now considered one of the most invasive species in the world because it can compete with native turtle species. In the present study, our objectives were to identify the potential for polystome spillover and spillback resulting from the introduction of the red-eared slider into new environments in North America. Fieldwork investigations were thus conducted mainly in aquatic habitats in Florida and North Carolina, United States, but also in Connecticut, Indiana, Kansas, Maine, Nebraska and New York. Using DNA barcoding based on cytochrome c oxidase I (COI) sequences, we surveyed the species diversity of polystome within American freshwater turtles. These included T. s. elegans but also Apalone ferox, Apalone spinifera, Chelydra serpentina, Chrysemys picta, Kinosternon baurii, Pseudemys spp., Sternotherus minor and Sternotherus odoratus. Genetic evidence confirmed that invasive populations of T. s. elegans in southern Europe have transmitted their own polystomes to native host species following spillover effects, and revealed here that T. s. elegans in non-indigenous habitats in the United States acts as a new reservoir of infection for native polystomes following spillback effects, thus increasing indigenous parasite transmission in the wild. Together, these findings raise further concern about the spread of non-native turtles and their impact on parasite transmission.